Serum levels of retinol-binding protein 4 and adiponectin in women with polycystic ovary syndrome: associations with visceral fat but no evidence for fat mass-independent effects on pathogenesis in this condition. - Barber, T; Hazell, M; Christodoulides, C; Golding, S; Alvey, C; Burling, K; Vidal-Puig, A; Groome, N; Wass, J; Franks, S; McCarthy, M (2008)
CONTEXT: Insulin resistance, which associates with levels of retinol-binding protein 4 (RBP4) and adiponectin, is implicated in the development of polycystic ovary syndrome (PCOS). OBJECTIVE: The objective of the study was to explore the potential contribution of RBP4 and adiponectin in the etiology of PCOS and their relationships with specific fat depot measurements. DESIGN: This was a cross-sectional study. SETTING AND PARTICIPANTS: Serum RBP4 and adiponectin levels were compared between 50 PCOS cases and 28 female controls (including 22 body mass index/fat mass-matched pairs) and correlated with specific fat depot (including visceral) axial magnetic resonance imaging cross-sectional area measurements. All subjects were of U.K. British/Irish origin. MAIN OUTCOME MEASURE(S): Serum levels of RBP4 (automated immunonephelometric assay) and adiponectin [immunoassay: total and high molecular weight (HMW)]. Data are reported as geometric mean (sd, range) and optionally adjusted for fat mass and age. RESULTS: Between the 50 PCOS cases and 28 controls, serum RBP4 levels were indistinguishable [39.0 microg/ml (31.0, 49.0) vs. 41.6 microg/ml (32.7, 52.9), respectively, unadjusted P = 0.24; adjusted P = 0.55]. Total (and HMW) adiponectin levels were lower in PCOS cases [total adiponectin 19.9 microg/ml (14.2, 27.8) vs. 25.8 microg/ml (17.7, 37.7), respectively, unadjusted P = 2.4 x 10(-3); adjusted P = 0.10]. For the paired-sample analyzes, there were no differences in RBP4 (P = 0.09), total adiponectin (P = 0.06), HMW adiponectin (P =0.19), or HMW to total adiponectin ratio (P = 0.98). In PCOS cases, L4-visceral fat area was associated positively with RBP4 (r(2) = 0.34, P = 0.01) and negatively with HMW to total adiponectin ratio (r(2) = -0.44, P = 1.3 x 10(-3)). Controls showed similar relationships. CONCLUSIONS: Although associated with visceral fat, serum RBP4 and adiponectin levels do not play important, fat-mass-independent primary roles in the development of PCOS.